Cover Image. Issue 3 (8th August 2019) - Khagi, Bijen; Kwon, Goo‐Rak; Lama, Ramesh
Abstract : Cover illustration: The cover image is based on the Research Article Comparative analysis of Alzheimer's disease classification by CDR level using CNN, feature selection, and machine-learning techniques by Bijen Khagi et al., https://doi.org/10.1002/ima.22316 .